The geographical dimension of biological invasions in the Anthropocene: the case of Xylella fastidiosa - Oliver Gutiérrez Hernández; Luis V. García (Boletín de la Asociación de Geógrafos Españoles, 2019)
Xylella fastidiosa is a potentially harmful organism for a large number of woody crops and tree species, being considered one of the most dangerous phytopathogenic bacteria worldwide. In this article, we used Ecological Niche Models (ENM) to predict the global potential distribution of X. fastidiosa, and at the regional level, Multi Criteria Evaluation (MCE) methods to predict the risk of exposure to this pathogen in the Iberian Peninsula and Balearic Islands. At the global level, our models predicted a wide potential distribution of X. fastidiosa with a wide potential radius of expansion temperate climates (Group C, Köppen climate classification). At regional level, our results revealed the Iberian Peninsula is very exposed to the entry and spread of this invasive organism, whose presence is already widespread in the Balearic Islands. In the Anthropocene epoch, Geography plays a crucial role in a management of biological risks because of a successful management depends heavily on our ability to predict potential geographical ranges of invasive organisms and to identify main factors that promote their spread.